Convergence of social and information technologies and the problem of trust in a digital society - Belаkrylаva Vera A.; Dabrarodni, Danila G. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The article deals with the problem of social trust in the context of convergent development of information and social technologies. Trust is the foundation of both interpersonal and institutional relationships. The trend of delegating the production of social trust to the technological sphere has emerged at the present stage. The convergence of information and social technologies has made it possible to create a comprehensive social credit system in China, designed to ensure a high level of social trust in the conditions of modernisation of society and transformation of the system of values and norms. The article analyses the possible risks of implementing such a system: shortcomings of the data collection methodology, monopolisation of control over the system and participants, leakage of personal data, the human factor, substitution of moral and legal regulations and the formation of a conformist model of behaviour. The authors formulate requirements that can reduce the risks of using the social rating system and preserve its fundamental setting – increasing the level of social trust. The specifics of centripetal (Chinese) and centrifugal (based on blockchain technology) models of trust in a digital society are determined.